2013
DOI: 10.1039/c3sm51054a
|View full text |Cite
|
Sign up to set email alerts
|

Single amino acid based self-assembled structure

Abstract: Single amino acids (phenylalanine, tyrosine and glycine) have been evaluated for fibrillar structure under neutral, aqueous conditions using scanning electron microscopy, transmission electron microscopy, circular dichroism, FTIR, and Congo red and thioflavin T histological dye assays. All these techniques prove that aromatic amino acids, such as phenylalanine and tyrosine, do in fact form distinct fibrillar structures albeit without any secondary structural characteristics such as an a-helix or a b-sheet. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 30 publications
1
91
0
Order By: Relevance
“…[33] They obtained straight fibers with a flat ribbon-like textures from a 1 mM solution of Tyr in deionized water. However, they did not find any signature of secondary structural characteristics.…”
Section: Amino Acid Based Nanostructuresmentioning
confidence: 99%
“…[33] They obtained straight fibers with a flat ribbon-like textures from a 1 mM solution of Tyr in deionized water. However, they did not find any signature of secondary structural characteristics.…”
Section: Amino Acid Based Nanostructuresmentioning
confidence: 99%
“…Weak interactions between complimentary amino acids occur in nature and their importance has been demonstrated in many biological processes, such as protein folding. These essential building blocks of life have their function dictated by the type of amino acids and interactions participating in their stabilisation …”
Section: Introductionmentioning
confidence: 99%
“…as producing a hydrogel containing crystals (the material was named a gel‐crystal) . The importance of investigating hydrogelation of Phe was raised recently when several studies correlated the aggregation of Phe with phenylketonuria and β‐amyloid‐based neurodegenerative conditions, such as Alzheimer's and Huntington's diseases . Considering the pathological implications of aggregation of Phe and the potential applications of Phe‐based hydrogels as drug delivery matrices, we developed amino acid based multi‐component gelating systems.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that Tyr can form well‐ordered structures when deposited onto the different surfaces commonly used in transmission electron microscopy (TEM), atomic force microscopy (AFM), scanning electron microscopy (SEM), and optical microscopy. To date, only one study recently reported that Tyr can form distinct fibrillar structures 8. In addition, two independent studies have reported the adsorption of Tyr on metal surfaces, that is, Cu(111)9 and Ag(111) 10.…”
mentioning
confidence: 99%